Traditional Chinese Medicine nursing of a patient with ankylosing spondylitis (1例强直性脊柱炎患者的中医护理体会) - LU Lin (芦琳); TANG Ling (唐玲); LI Ye (李野); LI Suqian (李苏茜) (Association of Integrative Nursing, 2021)
This paper summarized the Traditional Chinese Medicine nursing measures for a patient with ankylosing spondylitis. Key issues of nursing included procedure of moxibustion and hot compress technique with Chinese herbal medicine package, targeted living guidance, dietary intervention, functional exercise and psychological care. Based on the TCM theory, moxibustion and hot compress technique with Chinese herbal medicine package is effective to relieve the pain induced by ankylosing spondylitis, and improve p function of waist joint and quality of life of the patient. (本文总结了强直性脊柱炎(AS)的相关护理经验, 包括艾灸、中药热奄包的操作方法和注意事项以及针对性的生活指导、饮食调护、功能锻炼、心理干预等护理措施。基于中医理论指导, 开展艾灸及中药热奄包干预有助于改善AS患者疼痛症状, 改善腰部功能, 提高日常活动能力。)